A sodium ion battery

By controlling the ratio of the unit cell volume change rate and capacity contribution of the positive electrode active material, the problem of poor structural stability of the positive electrode active material of sodium ion battery is solved, and the effect of improving the cycle life of sodium ion battery is achieved.

CN117199341BActive Publication Date: 2025-02-14CALB GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311259586.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-02-14
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

During the charging and discharging process of sodium ion batteries, the structural stability of the positive electrode active material is poor, resulting in poor circulation performance.

Method used

By controlling the ratio of the unit cell volume change rate and capacity contribution of the positive electrode active material, structural stability at high voltage is ensured, thereby improving the cycle life of the sodium ion battery.

Benefits of technology

It effectively improves the cycle life of sodium ion batteries and ensures the stability of the positive electrode active material at high voltage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004472394640000191
    Figure BDA0004472394640000191
  • Figure FDA0005202961780000011
    Figure FDA0005202961780000011
  • Figure FDA0005202961780000012
    Figure FDA0005202961780000012
Patent Text Reader

Abstract

The present invention discloses a sodium ion battery, which comprises a positive electrode sheet, a positive electrode current collector and a positive electrode active material layer arranged on two opposite surfaces of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material; a negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer arranged on two opposite surfaces of the negative electrode current collector; and a ratio a of a unit cell volume change rate to a capacity contribution of the positive electrode active material satisfies 0.05≤a≤0.14. The sodium ion battery of the present invention improves the structural stability of the positive electrode active material under high voltage by controlling the ratio of the unit cell volume change rate to the capacity contribution of the positive electrode active material, thereby improving the cycle life of the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a sodium ion battery. Background Art

[0002] Sodium-ion batteries rely on the movement of sodium ions between the positive and negative electrodes to charge and discharge. During charging, sodium ions are released from the positive electrode and embedded in the negative electrode through the electrolyte. During discharging, sodium ions are released from the negative electrode and embedded in the positive electrode through the electrolyte.

[0003] As a key component of sodium-ion batteries, the positive electrode active material directly determines the energy density and cycle life of the entire battery system. Layered transition metal oxides with O3 phase provide open prismatic channels, low diffusion barriers and relatively high working potentials for sodium ion diffusion, making them very attractive candidate positive electrode active materials for sodium-ion batteries. However, during the charge and discharge process of sodium-ion batteries, the positive electrode active material will undergo an O3→P3→O3' phase transition. Especially when the charging voltage is greater than 4.0V, the reversibility of the P3→O3' phase transition of the positive electrode active material is low, resulting in changes in the crystal structure and unit cell volume of the positive electrode active material, resulting in microcracks, and as the sodium-ion battery charge and discharge cycle occurs, the microcracks gradually expand, resulting in poor structural stability of the positive electrode active material, which ultimately affects the cycle performance of the sodium-ion battery. Summary of the invention

[0004] In order to solve the above-mentioned defects in the prior art, an object of the present invention is to provide a sodium ion battery having higher cycle performance.

[0005] The technical solution provided according to the purpose of the present invention is as follows:

[0006] A sodium ion battery, comprising:

[0007] A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on two opposite surfaces of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material;

[0008] A negative electrode sheet, comprising a negative electrode current collector and negative electrode active material layers disposed on two opposite surfaces of the negative electrode current collector;

[0009] The ratio a of the unit cell volume change rate V and the capacity contribution C of the positive electrode active material satisfies 0.05≤a≤0.14;

[0010] Among them, the unit cell volume change rate of the positive electrode active material V1 is the unit cell volume of the positive electrode active material of the positive electrode sheet when the sodium ion battery is discharged to 2.0V and then disassembled, and the positive electrode sheet is assembled into a button battery, and the positive electrode sheet is charged to 4.0V in the second cycle of the charge and discharge cycle; V2 is the unit cell volume of the positive electrode active material of the positive electrode sheet when the same sodium ion battery is discharged to 2.0V and then disassembled, and the positive electrode sheet is assembled into a button battery, and the positive electrode sheet is charged to 4.2V in the second cycle of the charge and discharge cycle;

[0011] Capacity Contribution C1 is the capacity of the sodium ion battery in the 4.0-4.2V voltage range during the second charging process in the three charge and discharge cycles of 1C CC to 4.2V, CV to 0.05C, rest 10min, 1C DC to 2.00V, rest 10min. C2 is the capacity of the sodium ion battery in the 2-4.2V voltage range during the second charging process in the three charge and discharge cycles of 1C CC to 4.2V, CV to 0.05C, rest 10min, 1C DC to2.00V, rest 10min.

[0012] The sodium ion battery of the present invention improves the structural stability of the positive electrode active material at high voltage by controlling the ratio of the unit cell volume change rate to the capacity contribution of the positive electrode active material, thereby improving the cycle life of the sodium ion battery. DETAILED DESCRIPTION

[0013] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0014] In the present invention, CNT is carbon nanotube, PVDF is polyvinylidene fluoride, CMC is carboxymethyl cellulose, SBR is styrene butadiene rubber, and NMP is N-methyl pyrrolidone.

[0015] Example 1

[0016] This embodiment provides a method for preparing a sodium ion battery, comprising the following steps:

[0017] 1) Preparation of positive electrode active material: Ni SO4·6H2O, FeSO4·7H2O and MnSO4·H2O with a total concentration of 2.0M were weighed in a continuous stirred tank reactor at a molar ratio of 0.4:0.26:0.34 by a coprecipitation method, and a 2.0M sodium hydroxide solution was added to the continuous stirred tank reactor to prepare a mixed solution, and then the mixed solution was transferred to a storage tank, and then transferred to a reactor for heating under nitrogen protection, and the concentration of the complexing agent ammonia water was controlled to be 0.4M, the pH value was 12.5 and the reaction temperature was 50°C. After aging, the obtained powder was filtered, washed with deionized water, and dried in air at 100°C. The ternary precursor (Ni 0.4 Fe 0.26 Mn 0.34 )(OH)2;

[0018] The ternary precursor (Ni 0.4 Fe 0.26 Mn 0.34 )(OH)2 and sodium carbonate were uniformly mixed in a crucible in a molar ratio of 1:1, and placed in an atmosphere resistance furnace. The sintering temperature was controlled to be 950°C and the holding time was 15h. After the sintering was completed, it was cooled to room temperature, sieved, and sealed to obtain the positive electrode active material NaNi with a particle size D50 of 4.6μm. 0.4 Fe 0.26 Mn 0.34 O2.

[0019] 2) Preparation of positive electrode sheet: The positive electrode active material NaNi prepared in step 1) 0.4 Fe 0.26 Mn 0.34 O2, SuperP, conductive agent CNT, and binder PVDF were mixed in a mass ratio of 97.5:1:0.5:1, and the solid content of the slurry was controlled to be 70% to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil and dried, and rolled to obtain a positive electrode active material layer with a double-sided surface density of 312g / m 2 , compacted density is 3.5g / m 3 The positive electrode.

[0020] 3) Preparation of negative electrode active materials: Biomass raw materials such as coconut shells are carbonized at 600°C to synthesize charcoal, which is then graded after coarse and fine crushing, and then immersed in alkaline solution for 12 hours and dried at 120°C to obtain a powder. The powder is heated to 1300°C and kept warm for 2 hours for purification, and then modified to obtain hard carbon.

[0021] 4) Preparation of negative electrode sheet: prepare the hard carbon, Super P, CMC and SBR prepared in step 3) in a mass ratio of 96.1:0.8:1.5:1.6;

[0022] Add hard carbon and Super P according to the formula into a 5L stirring kettle, stir and dry mix to obtain dry powder;

[0023] Dissolve CMC in deionized water and disperse at 1800 rpm for 120 min to obtain a CMC glue solution with a solid content of 1.4%;

[0024] According to the formula, the dry powder, 50% CMC glue and 50% deionized water were mixed and stirred for 60 minutes, and the remaining 50% CMC glue and 50% deionized water were added, and the stirring was continued for 60 minutes. Then, SBR was added and stirred for 60 minutes, and then an appropriate amount of deionized water was added to adjust the viscosity to 3000-5000mPa.s to obtain a negative electrode slurry with a solid content of 50%;

[0025] The negative electrode slurry was evenly coated on the two opposite surfaces of the negative electrode current collector aluminum foil, and rolled to obtain a negative electrode active material layer with a double-sided surface density of 200 g / m 2 , compacted density is 1.0g / m 3 The negative electrode.

[0026] 5) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 3:5:2 to obtain an organic solvent, and then fully dried sodium salt NaPF6 is added to the organic solvent and stirred until the sodium salt NaPF6 is completely dissolved to prepare an electrolyte with a sodium salt NaPF6 concentration of 1 mol / L.

[0027] 6) Battery preparation: The positive electrode sheet of step 2), the ceramic diaphragm, and the negative electrode sheet of step 4) are stacked in sequence and put into a shell, and then liquid is injected, formed, and constant capacity is performed to obtain the sodium ion battery of this embodiment.

[0028] Example 2

[0029] This embodiment provides a method for preparing a sodium ion battery, comprising the following steps:

[0030] 1) Preparation of positive electrode active material: NiSO4·6H2O, FeSO4·7H2O and MnSO4·H2O with a total concentration of 2.0M were weighed in a continuous stirred tank reactor according to a molar ratio of 0.425:0.235:0.34 by a coprecipitation method, and a sodium hydroxide solution with a concentration of 2.0M was added to the continuous stirred tank reactor to prepare a mixed solution, and then the mixed solution was transferred to a storage tank, and then transferred to a reactor for heating under nitrogen protection, and the concentration of the complexing agent ammonia water was controlled to be 0.4M, the pH value was 12.5 and the reaction temperature was 50°C. After aging, the obtained powder was filtered, washed with deionized water, and dried in air at 100°C. The ternary precursor (Ni 0.425 Fe 0.235 Mn0.34 )(OH)2;

[0031] The ternary precursor (Ni 0.425 Fe 0.235 Mn 0.34 )(OH)2 and sodium carbonate were uniformly mixed in a crucible in a molar ratio of 1:1, and placed in an atmosphere resistance furnace. The sintering temperature was controlled to be 900°C and the holding time was 15h. After the sintering was completed, it was cooled to room temperature, sieved, and sealed to obtain the positive electrode active material NaNi with a particle size D50 of 4.5μm. 0.425 Fe 0.235 Mn 0.34 O2.

[0032] 2) Preparation of positive electrode sheet: The positive electrode active material NaNi prepared in step 1) 0.425 Fe 0.235 Mn 0.34 O2, Super P, conductive agent CNT, and binder PVDF were mixed in a mass ratio of 97.5:1:0.5:1, and the solid content of the slurry was controlled to be 70% to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil and dried, and rolled to obtain a positive electrode active material layer with a double-sided surface density of 312g / m 2 , compacted density is 3.5g / m 3 The positive electrode.

[0033] 3) Preparation of negative electrode active materials: Biomass raw materials such as coconut shells are carbonized at 600°C to synthesize charcoal, which is then graded after coarse and fine crushing, and then immersed in alkaline solution for 12 hours and dried at 120°C to obtain a powder. The powder is heated to 1300°C and kept warm for 2 hours for purification, and then modified to obtain hard carbon.

[0034] 4) Preparation of negative electrode sheet: prepare the hard carbon, Super P, CMC and SBR prepared in step 3) in a mass ratio of 96.1:0.8:1.5:1.6;

[0035] Add hard carbon and Super P according to the formula into a 5L stirring kettle, stir and dry mix to obtain dry powder;

[0036] Dissolve CMC in deionized water and disperse at 1800 rpm for 120 min to obtain a CMC glue solution with a solid content of 1.4%;

[0037] According to the formula, the dry powder, 50% CMC glue and 50% deionized water were mixed and stirred for 60 minutes, and the remaining 50% CMC glue and 50% deionized water were added, and the stirring was continued for 60 minutes. Then, SBR was added and stirred for 60 minutes, and then an appropriate amount of deionized water was added to adjust the viscosity to 3000-5000mPa.s to obtain a negative electrode slurry with a solid content of 50%;

[0038] The negative electrode slurry was evenly coated on the two opposite surfaces of the negative electrode current collector aluminum foil, and rolled to obtain a negative electrode active material layer with a double-sided surface density of 200 g / m 2 , compacted density is 1.0g / m 3 The negative electrode.

[0039] 5) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 3:5:2 to obtain an organic solvent, and then fully dried sodium salt NaPF6 is added to the organic solvent and stirred until the sodium salt NaPF6 is completely dissolved to prepare an electrolyte with a sodium salt NaPF6 concentration of 1 mol / L.

[0040] 6) Battery preparation: The positive electrode sheet of step 2), the ceramic diaphragm, and the negative electrode sheet of step 4) are stacked in sequence and put into a shell, and then liquid is injected, formed, and constant capacity is performed to obtain the sodium ion battery of this embodiment.

[0041] Example 3

[0042] This embodiment provides a method for preparing a sodium ion battery, comprising the following steps:

[0043] 1) Preparation of positive electrode active material: NiSO4·6H2O, FeSO4·7H2O and MnSO4·H2O with a total concentration of 2.0M were weighed in a continuous stirred tank reactor according to a molar ratio of 0.45:0.21:0.34 by a coprecipitation method, and a 2.0M sodium hydroxide solution was added to the continuous stirred tank reactor to prepare a mixed solution, and then the mixed solution was transferred to a storage tank, and then transferred to a reactor for heating under nitrogen protection, and the concentration of the complexing agent ammonia water was controlled to be 0.4M, the pH value was 12.5 and the reaction temperature was 50°C. After aging, the obtained powder was filtered, washed with deionized water, and dried in air at 100°C. The ternary precursor (Ni 0.45 Fe 0.21 Mn 0.34 )(OH)2;

[0044] The ternary precursor (Ni 0.45 Fe 0.21 Mn 0.34 )(OH)2 and sodium carbonate were uniformly mixed in a crucible in a molar ratio of 1:1, and placed in an atmosphere resistance furnace. The sintering temperature was controlled to be 1010°C and the holding time was 15h. After the sintering was completed, it was cooled to room temperature, sieved, and sealed to obtain the positive electrode active material NaNi with a particle size D50 of 4.8μm. 0.45 Fe 0.21 Mn 0.34 O2.

[0045] 2) Preparation of positive electrode sheet: The positive electrode active material NaNi prepared in step 1) 0.45 Fe 0.21 Mn 0.34 O2, Super P, conductive agent CNT, and binder PVDF were mixed in a mass ratio of 97.5:1:0.5:1, and the solid content of the slurry was controlled to be 70% to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil and dried, and rolled to obtain a positive electrode active material layer with a double-sided surface density of 312g / m 2 , compacted density is 3.5g / m 3 The positive electrode.

[0046] 3) Preparation of negative electrode active materials: Biomass raw materials such as coconut shells are carbonized at 600°C to synthesize charcoal, which is then graded after coarse and fine crushing, and then immersed in alkaline solution for 12 hours and dried at 120°C to obtain a powder. The powder is heated to 1300°C and kept warm for 2 hours for purification, and then modified to obtain hard carbon.

[0047] 4) Preparation of negative electrode sheet: prepare the hard carbon, Super P, CMC and SBR prepared in step 3) in a mass ratio of 96.1:0.8:1.5:1.6;

[0048] Add hard carbon and Super P according to the formula into a 5L stirring kettle, stir and dry mix to obtain dry powder;

[0049] Dissolve CMC in deionized water and disperse at 1800 rpm for 120 min to obtain a CMC glue solution with a solid content of 1.4%;

[0050] According to the formula, the dry powder, 50% CMC glue and 50% deionized water were mixed and stirred for 60 minutes, and the remaining 50% CMC glue and 50% deionized water were added, and the stirring was continued for 60 minutes. Then, SBR was added and stirred for 60 minutes, and then an appropriate amount of deionized water was added to adjust the viscosity to 3000-5000mPa.s to obtain a negative electrode slurry with a solid content of 50%;

[0051] The negative electrode slurry was evenly coated on the two opposite surfaces of the negative electrode current collector aluminum foil, and rolled to obtain a negative electrode active material layer with a double-sided surface density of 200 g / m 2 , compacted density is 1.0g / m 3 The negative electrode.

[0052] 5) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 3:5:2 to obtain an organic solvent, and then fully dried sodium salt NaPF6 is added to the organic solvent and stirred until the sodium salt NaPF6 is completely dissolved to prepare an electrolyte with a sodium salt NaPF6 concentration of 1 mol / L.

[0053] 6) Battery preparation: The positive electrode sheet of step 2), the ceramic diaphragm, and the negative electrode sheet of step 4) are stacked in sequence and put into a shell, and then liquid is injected, formed, and constant capacity is performed to obtain the sodium ion battery of this embodiment.

[0054] Example 4

[0055] This embodiment provides a method for preparing a sodium ion battery, comprising the following steps:

[0056] 1) Preparation of positive electrode active material: NiSO4·6H2O, FeSO4·7H2O and MnSO4·H2O with a total concentration of 2.0M were weighed in a continuous stirred tank reactor according to a molar ratio of 0.35:0.31:0.34 by a coprecipitation method, and a sodium hydroxide solution with a concentration of 2.0M was added to the continuous stirred tank reactor to prepare a mixed solution, and then the mixed solution was transferred to a storage tank, and then transferred to a reactor for heating under nitrogen protection, and the concentration of the complexing agent ammonia water was controlled to be 0.4M, the pH value was 12.5 and the reaction temperature was 50°C. After aging, the obtained powder was filtered, washed with deionized water, and dried in air at 100°C. The ternary precursor (Ni 0.35 Fe 0.31 Mn 0.34 )(OH)2;

[0057] The ternary precursor (Ni 0.35 Fe 0.31 Mn 0.34 )(OH)2 and sodium carbonate were uniformly mixed in a crucible in a molar ratio of 1:1, and placed in an atmosphere resistance furnace. The sintering temperature was controlled to be 975°C and the holding time was 15h. After the sintering was completed, it was cooled to room temperature, sieved, and sealed to obtain the positive electrode active material NaNi with a particle size D50 of 4.7μm. 0.35 Fe 0.31 Mn 0.34 O2.

[0058] 2) Preparation of positive electrode sheet: The positive electrode active material NaNi prepared in step 1) 0.35 Fe 0.31 Mn 0.34 O2, Super P, conductive agent CNT, and binder PVDF were mixed in a mass ratio of 97.5:1:0.5:1, and the solid content of the slurry was controlled to be 70% to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil and dried, and rolled to obtain a positive electrode active material layer with a double-sided surface density of 312g / m 2 , compacted density is 3.5g / m 3 The positive electrode.

[0059] 3) Preparation of negative electrode active materials: Biomass raw materials such as coconut shells are carbonized at 600°C to synthesize charcoal, which is then graded after coarse and fine crushing, immersed in alkaline solution for 12 hours, and dried at 120°C to obtain a powder. The powder is heated to 1300°C and kept warm for 2 hours for purification, and then modified to obtain hard carbon.

[0060] 4) Preparation of negative electrode sheet: prepare the hard carbon, Super P, CMC and SBR prepared in step 3) in a mass ratio of 96.1:0.8:1.5:1.6;

[0061] Add hard carbon and Super P according to the formula into a 5L stirring kettle, stir and dry mix to obtain dry powder;

[0062] Dissolve CMC in deionized water and disperse at 1800 rpm for 120 min to obtain a CMC glue solution with a solid content of 1.4%;

[0063] According to the formula, the dry powder, 50% CMC glue and 50% deionized water were mixed and stirred for 60 minutes, and the remaining 50% CMC glue and 50% deionized water were added, and the stirring was continued for 60 minutes. Then, SBR was added and stirred for 60 minutes, and then an appropriate amount of deionized water was added to adjust the viscosity to 3000-5000mPa.s to obtain a negative electrode slurry with a solid content of 50%;

[0064] The negative electrode slurry was evenly coated on the two opposite surfaces of the negative electrode current collector aluminum foil, and rolled to obtain a negative electrode active material layer with a double-sided surface density of 200 g / m 2 , compacted density is 1.0g / m 3 The negative electrode.

[0065] 5) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 3:5:2 to obtain an organic solvent, and then fully dried sodium salt NaPF6 is added to the organic solvent and stirred until the sodium salt NaPF6 is completely dissolved to prepare an electrolyte with a sodium salt NaPF6 concentration of 1 mol / L.

[0066] 6) Battery preparation: The positive electrode sheet of step 2), the ceramic diaphragm, and the negative electrode sheet of step 4) are stacked in sequence and put into a shell, and then liquid is injected, formed, and constant capacity is performed to obtain the sodium ion battery of this embodiment.

[0067] Example 5

[0068] This embodiment provides a method for preparing a sodium ion battery, comprising the following steps:

[0069] 1) Preparation of positive electrode active material: NiSO4·6H2O, FeSO4·7H2O and MnSO4·H2O with a total concentration of 2.0M were weighed in a continuous stirred tank reactor according to a molar ratio of 0.4:0.26:0.34 by a coprecipitation method, and a 2.0M sodium hydroxide solution was added to the continuous stirred tank reactor to prepare a mixed solution, and then the mixed solution was transferred to a storage tank, and then transferred to a reactor for heating under nitrogen protection, and the concentration of the complexing agent ammonia water was controlled to be 0.4M, the pH value was 12.5 and the reaction temperature was 50°C. After aging, the obtained powder was filtered, washed with deionized water, and dried in air at 100°C. The ternary precursor (Ni 0.4 Fe 0.26 Mn 0.34 )(OH)2;

[0070] The ternary precursor (Ni 0.4 Fe 0.26 Mn 0.34 )(OH)2 and sodium carbonate were uniformly mixed in a crucible in a molar ratio of 1:1, and placed in an atmosphere resistance furnace. The sintering temperature was controlled to be 975°C and the holding time was 15h. After the sintering was completed, it was cooled to room temperature, sieved, and sealed to obtain the positive electrode active material NaNi with a particle size D50 of 4.5μm. 0.4 Fe 0.26 Mn 0.34 O2.

[0071] 2) Preparation of positive electrode sheet: The positive electrode active material NaNi prepared in step 1) 0.4 Fe 0.26 Mn 0.34 O2, Super P, conductive agent CNT, and binder PVDF were mixed in a mass ratio of 97.5:1:0.5:1, and the solid content of the slurry was controlled to be 70% to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil and dried, and rolled to obtain a positive electrode active material layer with a double-sided surface density of 312g / m 2 , compacted density is 3.5g / m 3 The positive electrode.

[0072] 3) Preparation of negative electrode active materials: Biomass raw materials such as coconut shells are carbonized at 600°C to synthesize charcoal, which is then graded after coarse and fine crushing, immersed in alkaline solution for 12 hours, and dried at 120°C to obtain a powder. The powder is heated to 1300°C and kept warm for 2 hours for purification, and then modified to obtain hard carbon.

[0073] 4) Preparation of negative electrode sheet: prepare the hard carbon, Super P, CMC and SBR prepared in step 3) in a mass ratio of 96.1:0.8:1.5:1.6;

[0074] Add hard carbon and Super P according to the formula into a 5L stirring kettle, stir and dry mix to obtain dry powder;

[0075] Dissolve CMC in deionized water and disperse at 1800 rpm for 120 min to obtain a CMC glue solution with a solid content of 1.4%;

[0076] According to the formula, the dry powder, 50% CMC glue and 50% deionized water were mixed and stirred for 60 minutes, and the remaining 50% CMC glue and 50% deionized water were added, and the stirring was continued for 60 minutes. Then, SBR was added and stirred for 60 minutes, and then an appropriate amount of deionized water was added to adjust the viscosity to 3000-5000mPa.s to obtain a negative electrode slurry with a solid content of 50%;

[0077] The negative electrode slurry was evenly coated on the two opposite surfaces of the negative electrode current collector aluminum foil, and rolled to obtain a negative electrode active material layer with a double-sided surface density of 200 g / m 2 , compacted density is 1.0g / m 3 The negative electrode.

[0078] 5) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 3:5:2 to obtain an organic solvent, and then fully dried sodium salt NaPF6 is added to the organic solvent and stirred until the sodium salt NaPF6 is completely dissolved to prepare an electrolyte with a sodium salt NaPF6 concentration of 1 mol / L.

[0079] 6) Battery preparation: The positive electrode sheet of step 2), the ceramic diaphragm, and the negative electrode sheet of step 4) are stacked in sequence and put into a shell, and then liquid is injected, formed, and constant capacity is performed to obtain the sodium ion battery of this embodiment.

[0080] Example 6

[0081] This embodiment provides a method for preparing a sodium ion battery, comprising the following steps:

[0082] 1) Preparation of positive electrode active material: NiSO4·6H2O, FeSO4·7H2O and MnSO4·H2O with a total concentration of 2.0M were weighed in a continuous stirred tank reactor according to a molar ratio of 0.425:0.235:0.34 by a coprecipitation method, and a sodium hydroxide solution with a concentration of 2.0M was added to the continuous stirred tank reactor to prepare a mixed solution, and then the mixed solution was transferred to a storage tank, and then transferred to a reactor for heating under nitrogen protection, and the concentration of the complexing agent ammonia water was controlled to be 0.4M, the pH value was 12.5 and the reaction temperature was 50°C. After aging, the obtained powder was filtered, washed with deionized water, and dried in air at 100°C. The ternary precursor (Ni 0.425 Fe 0.235 Mn0.34 )(OH)2;

[0083] The ternary precursor (Ni 0.425 Fe 0.235 Mn 0.34 )(OH)2 and sodium carbonate were uniformly mixed in a crucible in a molar ratio of 1:1, and placed in an atmosphere resistance furnace. The sintering temperature was controlled to be 1010°C and the holding time was 15h. After the sintering was completed, it was cooled to room temperature, sieved, and sealed to obtain the positive electrode active material NaNi with a particle size D50 of 4.5μm. 0.425 Fe 0.235 Mn 0.34 O2.

[0084] 2) Preparation of positive electrode sheet: The positive electrode active material NaNi prepared in step 1) 0.425 Fe 0.235 Mn 0.34 O2, Super P, conductive agent CNT, and binder PVDF were mixed in a mass ratio of 97.5:1:0.5:1, and the solid content of the slurry was controlled to be 70% to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil and dried, and rolled to obtain a positive electrode active material layer with a double-sided surface density of 312g / m 2 , compacted density is 3.5g / m 3 The positive electrode.

[0085] 3) Preparation of negative electrode active materials: Biomass raw materials such as coconut shells are carbonized at 600°C to synthesize charcoal, which is then graded after coarse and fine crushing, immersed in alkaline solution for 12 hours, and dried at 120°C to obtain a powder. The powder is heated to 1300°C and kept warm for 2 hours for purification, and then modified to obtain hard carbon.

[0086] 4) Preparation of negative electrode sheet: prepare the hard carbon, Super P, CMC and SBR prepared in step 3) in a mass ratio of 96.1:0.8:1.5:1.6;

[0087] Add hard carbon and Super P according to the formula into a 5L stirring kettle, stir and dry mix to obtain dry powder;

[0088] Dissolve CMC in deionized water and disperse at 1800 rpm for 120 min to obtain a CMC glue solution with a solid content of 1.4%;

[0089] According to the formula, the dry powder, 50% CMC glue and 50% deionized water were mixed and stirred for 60 minutes, and the remaining 50% CMC glue and 50% deionized water were added, and the stirring was continued for 60 minutes. Then, SBR was added and stirred for 60 minutes, and then an appropriate amount of deionized water was added to adjust the viscosity to 3000-5000mPa.s to obtain a negative electrode slurry with a solid content of 50%;

[0090] The negative electrode slurry was evenly coated on the two opposite surfaces of the negative electrode current collector aluminum foil, and rolled to obtain a negative electrode active material layer with a double-sided surface density of 200 g / m 2 , compacted density is 1.0g / m 3 The negative electrode.

[0091] 5) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 3:5:2 to obtain an organic solvent, and then fully dried sodium salt NaPF6 is added to the organic solvent and stirred until the sodium salt NaPF6 is completely dissolved to prepare an electrolyte with a sodium salt NaPF6 concentration of 1 mol / L.

[0092] 6) Battery preparation: The positive electrode sheet of step 2), the ceramic diaphragm, and the negative electrode sheet of step 4) are stacked in sequence and put into a shell, and then liquid is injected, formed, and constant capacity is performed to obtain the sodium ion battery of this embodiment.

[0093] Example 7

[0094] This embodiment provides a method for preparing a sodium ion battery, comprising the following steps:

[0095] 1) Preparation of positive electrode active material: NiSO4·6H2O, FeSO4·7H2O and MnSO4·H2O with a total concentration of 2.0M were weighed in a continuous stirred tank reactor according to a molar ratio of 0.45:0.21:0.34 by a coprecipitation method, and a 2.0M sodium hydroxide solution was added to the continuous stirred tank reactor to prepare a mixed solution, and then the mixed solution was transferred to a storage tank, and then transferred to a reactor for heating under nitrogen protection, and the concentration of the complexing agent ammonia water was controlled to be 0.4M, the pH value was 12.5 and the reaction temperature was 50°C. After aging, the obtained powder was filtered, washed with deionized water, and dried in air at 100°C. The ternary precursor (Ni 0.45 Fe 0.21 Mn 0.34 )(OH)2;

[0096] The ternary precursor (Ni 0.45 Fe 0.21 Mn 0.34 )(OH)2 and sodium carbonate were uniformly mixed in a crucible in a molar ratio of 1:1, and placed in an atmosphere resistance furnace. The sintering temperature was controlled to be 975°C and the holding time was 15h. After the sintering was completed, it was cooled to room temperature, sieved, and sealed to obtain the positive electrode active material NaNi with a particle size D50 of 4.8μm. 0.45 Fe 0.21 Mn 0.34 O2.

[0097] 2) Preparation of positive electrode sheet: The positive electrode active material NaNi prepared in step 1) 0.45 Fe 0.21 Mn 0.34 O2, Super P, conductive agent CNT, and binder PVDF were mixed in a mass ratio of 97.5:1:0.5:1, and the solid content of the slurry was controlled to be 70% to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil and dried, and rolled to obtain a positive electrode active material layer with a double-sided surface density of 312g / m 2 , compacted density is 3.5g / m 3 The positive electrode.

[0098] 3) Preparation of negative electrode active materials: Biomass raw materials such as coconut shells are carbonized at 600°C to synthesize charcoal, which is then graded after coarse and fine crushing, immersed in alkaline solution for 12 hours, and dried at 120°C to obtain a powder. The powder is heated to 1300°C and kept warm for 2 hours for purification, and then modified to obtain hard carbon.

[0099] 4) Preparation of negative electrode sheet: prepare the hard carbon, Super P, CMC and SBR prepared in step 3) in a mass ratio of 96.1:0.8:1.5:1.6;

[0100] Add hard carbon and Super P according to the formula into a 5L stirring kettle, stir and dry mix to obtain dry powder;

[0101] Dissolve CMC in deionized water and disperse at 1800 rpm for 120 min to obtain a CMC glue solution with a solid content of 1.4%;

[0102] According to the formula, the dry powder, 50% CMC glue and 50% deionized water were mixed and stirred for 60 minutes, and the remaining 50% CMC glue and 50% deionized water were added, and the stirring was continued for 60 minutes. Then, SBR was added and stirred for 60 minutes, and then an appropriate amount of deionized water was added to adjust the viscosity to 3000-5000mPa.s to obtain a negative electrode slurry with a solid content of 50%;

[0103] The negative electrode slurry was evenly coated on the two opposite surfaces of the negative electrode current collector aluminum foil, and rolled to obtain a negative electrode active material layer with a double-sided surface density of 200 g / m 2 , compacted density is 1.0g / m 3 The negative electrode.

[0104] 5) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 3:5:2 to obtain an organic solvent, and then fully dried sodium salt NaPF6 is added to the organic solvent and stirred until the sodium salt NaPF6 is completely dissolved to prepare an electrolyte with a sodium salt NaPF6 concentration of 1 mol / L.

[0105] 6) Battery preparation: The positive electrode sheet of step 2), the ceramic diaphragm, and the negative electrode sheet of step 4) are stacked in sequence and put into a shell, and then liquid is injected, formed, and constant capacity is performed to obtain the sodium ion battery of this embodiment.

[0106] Example 8

[0107] This embodiment provides a method for preparing a sodium ion battery, comprising the following steps:

[0108] 1) Preparation of positive electrode active material: NiSO4·6H2O, FeSO4·7H2O and MnSO4·H2O with a total concentration of 2.0M were weighed in a continuous stirred tank reactor according to a molar ratio of 0.4:0.26:0.34 by a coprecipitation method, and a 2.0M sodium hydroxide solution was added to the continuous stirred tank reactor to prepare a mixed solution, and then the mixed solution was transferred to a storage tank, and then transferred to a reactor for heating under nitrogen protection, and the concentration of the complexing agent ammonia water was controlled to be 0.4M, the pH value was 12.5 and the reaction temperature was 50°C. After aging, the obtained powder was filtered, washed with deionized water, and dried in air at 100°C. The ternary precursor (Ni 0.4 Fe 0.26 Mn 0.34 )(OH)2;

[0109] The ternary precursor (Ni 0.4 Fe 0.26 Mn 0.34 )(OH)2 and sodium carbonate were uniformly mixed in a crucible in a molar ratio of 1:1, and placed in an atmosphere resistance furnace. The sintering temperature was controlled to be 950°C and the holding time was 15h. After the sintering was completed, it was cooled to room temperature, sieved, and sealed to obtain the positive electrode active material NaNi with a particle size D50 of 4.6μm. 0.4 Fe 0.26 Mn 0.34 O2.

[0110] 2) Preparation of positive electrode sheet: The positive electrode active material NaNi prepared in step 1) 0.4 Fe 0.26 Mn 0.34 O2, Super P, conductive agent CNT, and binder PVDF were mixed in a mass ratio of 97.5:1:0.5:1, and the solid content of the slurry was controlled to be 70% to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil and dried, and rolled to obtain a positive electrode active material layer with a double-sided surface density of 312g / m 2 , compacted density is 3.5g / m 3 The positive electrode.

[0111] 3) Preparation of negative electrode active materials: Biomass raw materials such as coconut shells are carbonized at 600°C to synthesize charcoal, which is then graded after coarse and fine crushing, immersed in alkaline solution for 12 hours, and dried at 120°C to obtain a powder. The powder is heated to 1300°C and kept warm for 2 hours for purification, and then modified to obtain hard carbon.

[0112] 4) Preparation of negative electrode sheet: prepare the hard carbon, Super P, CMC and SBR prepared in step 3) in a mass ratio of 96.1:0.8:1.5:1.6;

[0113] Add hard carbon and Super P according to the formula into a 5L stirring kettle, stir and dry mix to obtain dry powder;

[0114] Dissolve CMC in deionized water and disperse at 1800 rpm for 120 min to obtain a CMC glue solution with a solid content of 1.4%;

[0115] According to the formula, the dry powder, 50% CMC glue and 50% deionized water were mixed and stirred for 60 minutes, and the remaining 50% CMC glue and 50% deionized water were added, and the stirring was continued for 60 minutes. Then, SBR was added and stirred for 60 minutes, and then an appropriate amount of deionized water was added to adjust the viscosity to 3000-5000mPa.s to obtain a negative electrode slurry with a solid content of 50%;

[0116] The negative electrode slurry was evenly coated on the two opposite surfaces of the negative electrode current collector aluminum foil, and rolled to obtain a negative electrode active material layer with a double-sided surface density of 200 g / m 2 , compacted density is 1.0g / m 3 The negative electrode.

[0117] 5) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 3:5:2 to obtain an organic solvent, and then fully dried sodium salt NaPF6 is added to the organic solvent and stirred until the sodium salt NaPF6 is completely dissolved to prepare an electrolyte with a sodium salt NaPF6 concentration of 1 mol / L.

[0118] 6) Battery preparation: The positive electrode sheet of step 2), the ceramic diaphragm, and the negative electrode sheet of step 4) are stacked in sequence and put into a shell, and then liquid is injected, formed, and constant capacity is performed to obtain the sodium ion battery of this embodiment.

[0119] Comparative Example 1

[0120] This comparative example provides a method for preparing a sodium ion battery, comprising the following steps:

[0121] 1) Preparation of positive electrode active material: NiSO4·6H2O, FeSO4·7H2O and MnSO4·H2O with a total concentration of 2.0M were weighed in a continuous stirred tank reactor at a molar ratio of 0.33:0.33:0.34 by a coprecipitation method, and a 2.0M sodium hydroxide solution was added to the continuous stirred tank reactor to prepare a mixed solution, and then the mixed solution was transferred to a storage tank, and then transferred to a reactor for heating under nitrogen protection, and the concentration of the complexing agent ammonia water was controlled to be 0.4M, the pH value was 12.5 and the reaction temperature was 50°C. After aging, the obtained powder was filtered, washed with deionized water, and dried in air at 100°C. The ternary precursor (Ni 0.33 Fe 0.33 Mn 0.34 )(OH)2;

[0122] The ternary precursor (Ni 0.33 Fe 0.33 Mn 0.34 )(OH)2 and sodium carbonate were uniformly mixed in a crucible in a molar ratio of 1:1, and placed in an atmosphere resistance furnace. The sintering temperature was controlled to be 950°C and the holding time was 15h. After the sintering was completed, it was cooled to room temperature, sieved, and sealed to obtain the positive electrode active material NaNi with a particle size D50 of 12.3μm. 0.33 Fe 0.33 Mn 0.34 O2.

[0123] 2) Preparation of positive electrode sheet: The positive electrode active material NaNi prepared in step 1) 0.33 Fe 0.33 Mn 0.34 O2, Super P, conductive agent CNT, and binder PVDF were mixed in a mass ratio of 97.5:1:0.5:1, and the solid content of the slurry was controlled to be 70% to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil and dried, and rolled to obtain a positive electrode active material layer with a double-sided surface density of 312g / m 2 , compacted density is 3.5g / m 3 The positive electrode.

[0124] 3) Preparation of negative electrode active materials: Biomass raw materials such as coconut shells are carbonized at 600°C to synthesize charcoal, which is then graded after coarse and fine crushing, immersed in alkaline solution for 12 hours, and dried at 120°C to obtain a powder. The powder is heated to 1300°C and kept warm for 2 hours for purification, and then modified to obtain hard carbon.

[0125] 4) Preparation of negative electrode sheet: prepare the hard carbon, Super P, CMC and SBR prepared in step 3) in a mass ratio of 96.1:0.8:1.5:1.6;

[0126] Add hard carbon and Super P according to the formula into a 5L stirring kettle, stir and dry mix to obtain dry powder;

[0127] Dissolve CMC in deionized water and disperse at 1800 rpm for 120 min to obtain a CMC glue solution with a solid content of 1.4%;

[0128] According to the formula, the dry powder, 50% CMC glue and 50% deionized water were mixed and stirred for 60 minutes, and the remaining 50% CMC glue and 50% deionized water were added, and the stirring was continued for 60 minutes. Then, SBR was added and stirred for 60 minutes, and then an appropriate amount of deionized water was added to adjust the viscosity to 3000-5000mPa.s to obtain a negative electrode slurry with a solid content of 50%;

[0129] The negative electrode slurry was evenly coated on the two opposite surfaces of the negative electrode current collector aluminum foil, and rolled to obtain a negative electrode active material layer with a double-sided surface density of 200 g / m 2 , compacted density is 1.0g / m 3 The negative electrode.

[0130] 5) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 3:5:2 to obtain an organic solvent, and then fully dried sodium salt NaPF6 is added to the organic solvent and stirred until the sodium salt NaPF6 is completely dissolved to prepare an electrolyte with a sodium salt NaPF6 concentration of 1 mol / L.

[0131] 6) Battery preparation: The positive electrode sheet of step 2), the ceramic diaphragm, and the negative electrode sheet of step 4) are stacked in sequence and put into a shell, and then liquid injection, formation, and constant capacity are performed to obtain the sodium ion battery of this comparative example.

[0132] Comparative Example 2

[0133] This comparative example provides a method for preparing a sodium ion battery, comprising the following steps:

[0134] 1) Preparation of positive electrode active material: NiSO4·6H2O, FeSO4·7H2O and MnSO4·H2O with a total concentration of 2.0M were weighed in a continuous stirred tank reactor according to a molar ratio of 0.4:0.26:0.34 by a coprecipitation method, and a 2.0M sodium hydroxide solution was added to the continuous stirred tank reactor to prepare a mixed solution, and then the mixed solution was transferred to a storage tank, and then transferred to a reactor for heating under nitrogen protection, and the concentration of the complexing agent ammonia water was controlled to be 0.4M, the pH value was 12.5 and the reaction temperature was 50°C. After aging, the obtained powder was filtered, washed with deionized water, and dried in air at 100°C. The ternary precursor (Ni 0.4 Fe 0.26 Mn0.34 )(OH)2;

[0135] The ternary precursor (Ni 0.4 Fe 0.26 Mn 0.34 )(OH)2 and sodium carbonate were uniformly mixed in a crucible in a molar ratio of 1:1, and placed in an atmosphere resistance furnace. The sintering temperature was controlled to be 850°C and the holding time was 15h. After the sintering was completed, it was cooled to room temperature, sieved, and sealed to obtain the positive electrode active material NaNi with a particle size D50 of 4.5μm. 0.4 Fe 0.26 Mn 0.34 O2.

[0136] 2) Preparation of positive electrode sheet: The positive electrode active material NaNi prepared in step 1) 0.4 Fe 0.26 Mn 0.34 O2, Super P, conductive agent CNT, and binder PVDF were mixed in a mass ratio of 97.5:1:0.5:1, and the solid content of the slurry was controlled to be 70% to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil and dried, and rolled to obtain a positive electrode active material layer with a double-sided surface density of 312g / m 2 , compacted density is 3.5g / m 3 The positive electrode.

[0137] 3) Preparation of negative electrode active materials: Biomass raw materials such as coconut shells are carbonized at 600°C to synthesize charcoal, which is then graded after coarse and fine crushing, immersed in alkaline solution for 12 hours, and dried at 120°C to obtain a powder. The powder is heated to 1300°C and kept warm for 2 hours for purification, and then modified to obtain hard carbon.

[0138] 4) Preparation of negative electrode sheet: prepare the hard carbon, Super P, CMC and SBR prepared in step 3) in a mass ratio of 96.1:0.8:1.5:1.6;

[0139] Add hard carbon and Super P according to the formula into a 5L stirring kettle, stir and dry mix to obtain dry powder;

[0140] Dissolve CMC in deionized water and disperse at 1800 rpm for 120 min to obtain a CMC glue solution with a solid content of 1.4%;

[0141] According to the formula, the dry powder, 50% CMC glue and 50% deionized water were mixed and stirred for 60 minutes, and the remaining 50% CMC glue and 50% deionized water were added, and the stirring was continued for 60 minutes. Then, SBR was added and stirred for 60 minutes, and then an appropriate amount of deionized water was added to adjust the viscosity to 3000-5000mPa.s to obtain a negative electrode slurry with a solid content of 50%;

[0142] The negative electrode slurry was evenly coated on the two opposite surfaces of the negative electrode current collector aluminum foil, and rolled to obtain a negative electrode active material layer with a double-sided surface density of 200 g / m 2 , compacted density is 1.0g / m 3 The negative electrode.

[0143] 5) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 3:5:2 to obtain an organic solvent, and then fully dried sodium salt NaPF6 is added to the organic solvent and stirred until the sodium salt NaPF6 is completely dissolved to prepare an electrolyte with a sodium salt NaPF6 concentration of 1 mol / L.

[0144] 6) Battery preparation: The positive electrode sheet of step 2), the ceramic diaphragm, and the negative electrode sheet of step 4) are stacked in sequence and put into a shell, and then liquid injection, formation, and constant capacity are performed to obtain the sodium ion battery of this comparative example.

[0145] Comparative Example 3

[0146] This embodiment provides a method for preparing a sodium ion battery, comprising the following steps:

[0147] 1) Preparation of positive electrode active material: NiSO4·6H2O, FeSO4·7H2O and MnSO4·H2O with a total concentration of 2.0M were weighed in a continuous stirred tank reactor according to a molar ratio of 0.5:0.16:0.34 by a coprecipitation method, and a sodium hydroxide solution with a concentration of 2.0M was added to the continuous stirred tank reactor to prepare a mixed solution, and then the mixed solution was transferred to a storage tank, and then transferred to a reactor for heating under nitrogen protection, and the concentration of the complexing agent ammonia water was controlled to be 0.4M, the pH value was 12.5 and the reaction temperature was 50°C. After aging, the obtained powder was filtered, washed with deionized water, and dried in air at 100°C. The ternary precursor (Ni 0.5 Fe 0.16 Mn 0.34 )(OH)2;

[0148] The ternary precursor (Ni 0.5 Fe 0.16 Mn 0.34 )(OH)2 and sodium carbonate were uniformly mixed in a crucible in a molar ratio of 1:1, and placed in an atmosphere resistance furnace. The sintering temperature was controlled to be 1050°C and the holding time was 15h. After the sintering was completed, it was cooled to room temperature, sieved, and sealed to obtain the positive electrode active material NaNi with a particle size D50 of 13.2μm. 0.5 Fe 0.16 Mn 0.34 O2.

[0149] 2) Preparation of positive electrode sheet: The positive electrode active material NaNi prepared in step 1) 0.5 Fe 0.16 Mn 0.34 O2, Super P, conductive agent CNT, and binder PVDF were mixed in a mass ratio of 97.5:1:0.5:1, and the solid content of the slurry was controlled to be 70% to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the two opposite surfaces of the positive electrode current collector aluminum foil and dried, and rolled to obtain a positive electrode active material layer with a double-sided surface density of 312g / m 2 , compacted density is 3.5g / m 3 The positive electrode.

[0150] 3) Preparation of negative electrode active materials: Biomass raw materials such as coconut shells are carbonized at 600°C to synthesize charcoal, which is then graded after coarse and fine crushing, immersed in alkaline solution for 12 hours, and dried at 120°C to obtain a powder. The powder is heated to 1300°C and kept warm for 2 hours for purification, and then modified to obtain hard carbon.

[0151] 4) Preparation of negative electrode sheet: prepare the hard carbon, Super P, CMC and SBR prepared in step 3) in a mass ratio of 96.1:0.8:1.5:1.6;

[0152] Add hard carbon and Super P according to the formula into a 5L stirring kettle, stir and dry mix to obtain dry powder;

[0153] Dissolve CMC in deionized water and disperse at 1800 rpm for 120 min to obtain a CMC glue solution with a solid content of 1.4%;

[0154] According to the formula, the dry powder, 50% CMC glue and 50% deionized water were mixed and stirred for 60 minutes, and the remaining 50% CMC glue and 50% deionized water were added, and the stirring was continued for 60 minutes. Then, SBR was added and stirred for 60 minutes, and then an appropriate amount of deionized water was added to adjust the viscosity to 3000-5000mPa.s to obtain a negative electrode slurry with a solid content of 50%;

[0155] The negative electrode slurry was evenly coated on the two opposite surfaces of the negative electrode current collector aluminum foil, and rolled to obtain a negative electrode active material layer with a double-sided surface density of 200 g / m 2 , compacted density is 1.0g / m 3 The negative electrode.

[0156] 5) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 3:5:2 to obtain an organic solvent, and then fully dried sodium salt NaPF6 is added to the organic solvent and stirred until the sodium salt NaPF6 is completely dissolved to prepare an electrolyte with a sodium salt NaPF6 concentration of 1 mol / L.

[0157] 6) Battery preparation: The positive electrode sheet of step 2), the ceramic diaphragm, and the negative electrode sheet of step 4) are stacked in sequence and put into a shell, and then liquid is injected, formed, and constant capacity is performed to obtain the sodium ion battery of this embodiment.

[0158] The positive electrode active materials prepared in Examples 1-8 and Comparative Examples 1-3 have a phase with a Ni concentration gradient, which is a layered phase Na y Ni x Fe 0.66-x Mn 0.34 O2 (0.9≤y≤1.1, 0.35≤x≤0.45), layered phase and rock salt phase transition phase, rock salt phase NiO, layered phase and rock salt phase transition phase is located at (95%-96%)R-(97%-99.8%)R from the core of the positive electrode active material particle. Specifically, the phases with Ni concentration gradient changes in the positive electrode active material are layered phase Na at 0-99%R from the core of the positive electrode active material particle. y Ni x Fe 0.66-x Mn 0.34 O2 (0.9≤y≤1.1, 0.35≤x≤0.45), the layered phase and the rock salt phase transition phase at 99%-99.7%R from the core of the positive electrode active material particle, and the rock salt phase NiO at 99.7%-100%R from the core of the positive electrode active material particle. R is the minimum circumscribed circle radius of the positive electrode active material.

[0159] The Ni concentration of the present invention is the molar ratio of Ni in the transition metal element in the positive electrode active material, wherein the molar ratio of Ni in the transition metal element in the layered phase is 30%-36%, indicating that the presence of the rock salt phase does not affect the composition and structure of the internal layered phase. The molar ratio of Ni in the transition metal element in the transition phase between the layered phase and the rock salt phase is 60%-70%, indicating that there is a transition phase between the layered phase and the rock salt phase, and the layered phase and the rock salt phase are not completely separated. The molar ratio of Ni in the transition metal element in the rock salt phase is 90%-100%, indicating that the rock salt phase is fully formed. The present invention selects three points in each of the three phase regions to perform EDS testing on the cross-section of the positive electrode active material prepared in Examples 1-8 and Comparative Examples 1-3 to obtain the molar ratio of Ni in the transition metal element.

[0160] It should be noted that the positive electrode active material Na y Ni x Fe 0.66-x Mn 0.34In O2 (0.9≤y≤1.1, 0.35≤x≤0.45), 0.9≤y≤1.1 is limited to ensure that the positive electrode active material is an O3 phase structure, and the manganese content is limited to be fixed so that the positive electrode active material maintains a relatively stable structure. This is because manganese is not easily dissolved in the positive electrode active material, while iron is easily dissolved.

[0161] Table 1 shows the parameter characteristics of the positive electrode active materials of Examples 1-8 and Comparative Examples 1-3.

[0162] Table 1

[0163]

[0164] Performance testing and analysis

[0165] 1. Test objects: positive electrode active materials and sodium ion batteries prepared in Examples 1-8 and Comparative Examples 1-3.

[0166] 2. Test items

[0167] 1) Test of the volume change rate of the unit cell of the positive electrode active material

[0168] Two groups of positive electrode active materials of Examples 1-8 and Comparative Examples 1-3 prepared in the same batch were prepared to prepare two groups of sodium ion batteries, and the two groups of sodium ion batteries were cycled according to the cycle steps, first charged to a full state, then discharged to 2.0V, and then the two groups of sodium ion batteries were disassembled to obtain two groups of used positive electrode sheets. The two groups of used positive electrode sheets were assembled according to the assembly process of button batteries, one group of button batteries was disassembled when charged to 4.0V in the second cycle of charge and discharge cycle, and the other group of button batteries was disassembled when charged to 4.2V in the second cycle of charge and discharge cycle.

[0169] The positive electrode sheet charged to 4.0V and the positive electrode sheet charged to 4.2V were subjected to XRD test according to the following steps:

[0170] Step 1, sample processing and loading: fix the cathode sample on the glass sample holder, then insert the sample holder into the sample card slot, and close the sample chamber door;

[0171] Step 2, software step setting: open the measurement control system software and enter the control main interface. The diffractometer uses Cu-Kα line as the diffraction source, sets the working voltage to 40kV, the working current to 40mA, the scanning speed of the diffractometer to 10° / min, the scanning range to 10°-90°, set the start and end angles, and the scanning speed to 0.05℃ / min;

[0172] Step 3: After the instrument prompts that the test is completed and the X-ray in the sample chamber is turned off, you can open the sample chamber, take out the sample rack, and recycle the sample;

[0173] Step 4: Process the image by smoothing, filtering, and background subtraction, use VESTA to construct the basic structure of the synthesized material, and then use GENERAL STRUCTURE ANALYSIS SYSTEM software (GSAS) to refine the XRD spectrum. Use the least squares method to adjust the atomic parameters in the structure, the peak parameters used for fitting, and the instrument parameters, so that the weighted residual variance factor Rwp of the whole spectrum is minimized. After the refinement meets the requirements, the structural data is exported and analyzed and plotted using VESTA;

[0174] STEP5: Calculate the unit cell volume change rate based on the exported structural data Wherein, V1 is the unit cell volume of the positive electrode active material on the positive electrode sheet that was charged to 4.0V and disassembled, and V2 is the unit cell volume of the positive electrode active material on the positive electrode sheet that was charged to 4.2V and disassembled.

[0175] 2) Capacity contribution

[0176] Follow the steps below to assemble the button cell battery:

[0177] a. Preparation of positive electrode sheet: The positive electrode active materials of Examples 1-8 and Comparative Examples 1-3 were mixed with conductive carbon and binder PVDF in a mass ratio of 90:5:5 in an appropriate amount of NMP solvent and stirred to form a uniform positive electrode slurry; the positive electrode slurry was coated on the positive electrode current collector carbon-coated aluminum foil, and after drying, it was punched into small discs with a diameter of 14 mm;

[0178] b. Negative electrode: Use metallic sodium plate;

[0179] c. Diaphragm: Glass fiber;

[0180] d. Electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate were mixed in a volume ratio of 3:5:2 to obtain an organic solvent, and then fully dried sodium salt NaPF6 was added to the organic solvent, and stirred until the sodium salt NaPF6 was completely dissolved to prepare a sodium salt NaPF6 concentration of 1 mol / L electrolyte for standby use;

[0181] e. Preparation of button cells: first place the positive electrode shell stably, and stack the positive electrode sheet, separator, and negative electrode sheet on the positive electrode shell in order. The separator is placed between the positive electrode sheet and the negative electrode sheet to serve as an isolation. The electrolyte is injected into the positive electrode shell, and the negative electrode shell is covered. The button cells corresponding to Examples 1-8 and Comparative Examples 1-3 are obtained by packaging.

[0182] The button cells of Examples 1-8 and Comparative Examples 1-3 were subjected to cycle tests in a constant temperature environment at 25°C. The test procedure was: 1C CC to 4.2V, CV to 0.05C, rest 10min, 1C DC to 2.00V, rest 10 min, 3 cycles, C1 was the capacity of the button cells of Examples 1-8 and Comparative Examples 1-3 in the second cycle of charging in the voltage range of 4.0-4.2V, C2 was the capacity of the button cells of Examples 1-8 and Comparative Examples 1-3 in the second cycle of charging in the voltage range of 2-4.2V, and the capacity contribution was defined as

[0183] Definition: The ratio of the volume change rate of the unit cell of the positive electrode active material to its capacity contribution is a, a=V / C.

[0184] 3) Cycle performance

[0185] The sodium ion batteries of Examples 1-8 and Comparative Examples 1-3 were subjected to charge and discharge cycle tests in a constant temperature environment of 25°C. The charge and discharge process was: 1C CC to 4.2V, CV to 0.05C, rest 10min, 1C DC to 2.00V, rest10min. When the capacity decayed to 80% of the initial capacity, the number of cycles was recorded.

[0186] 3. Test results: See Table 2.

[0187] Table 2

[0188] V C a Cycle performance / cycle Example 1 0.005 0.1 0.05 100 Example 2 0.0075 0.08 0.09 80 Example 3 0.01 0.07 0.14 70 Example 4 0.006 0.075 0.08 90 Example 5 0.004 0.08 0.05 75 Example 6 0.014 0.1 0.14 65 Example 7 0.005 0.06 0.08 85 Example 8 0.01 0.12 0.08 80 Comparative Example 1 0.015 0.05 0.30 50 Comparative Example 2 0.02 0.04 0.50 25 Comparative Example 3 0.025 0.04 0.625 20

[0189] It can be seen from Table 2 that the cycle performance of the sodium ion batteries of Examples 1-8 is significantly better than that of Comparative Examples 1-3. The ratio of the volume change rate of the positive electrode active material unit cell to the capacity contribution of Examples 1-8 satisfies 0.05≤a≤0.14, which is significantly smaller than 0.30 of Comparative Example 1, 0.50 of Comparative Example 2, and 0.625 of Comparative Example 3, indicating that the smaller the ratio of the volume change rate of the positive electrode active material unit cell to the capacity contribution, the better the structural stability of the positive electrode active material, and thus the higher the cycle life of the prepared sodium ion battery.

[0190] Further, the unit cell volume change rate of the positive electrode active material of Examples 1-8 satisfies 0.005≤V≤0.014, which is less than 0.015 of Comparative Example 1, 0.02 of Comparative Example 2, and 0.025 of Comparative Example 3, and the capacity contribution of Examples 1-4 satisfies 0.06≤C≤0.12, which is greater than 0.05 of Comparative Example 1, and 0.04 of Comparative Example 2 and Comparative Example 3. This shows that the smaller the unit cell volume change rate of the positive electrode active material, the more stable the structure of the positive electrode active material, the higher the capacity contribution, and the more conducive to improving the working performance of the sodium ion battery at high voltage, so that the combination of the two is conducive to improving the cycle performance of the sodium ion battery.

[0191] More preferably, the cycle performance of Examples 1-2, 4, and 7-8 is better than that of Examples 3 and 5-6, indicating that the ratio of the unit cell volume change rate of the positive electrode active material to the capacity contribution is preferably 0.05≤a≤0.09, and the unit cell volume change rate of the positive electrode active material is preferably 0.005≤V≤0.01, and the capacity contribution is preferably 0.06≤C≤0.12.

[0192] Most preferably, the sodium ion batteries of Example 1 and Example 4 have the best cycle performance, indicating that the ratio of the unit cell volume change rate of the positive electrode active material to the capacity contribution is preferably 0.05≤a≤0.08, and the unit cell volume change rate of the positive electrode active material is preferably 0.005≤V≤0.006, and the capacity contribution is preferably 0.075≤C≤0.1.

[0193] Referring to Table 1 and Table 2, the sodium ion batteries of Examples 1-8 and Comparative Examples 1-3 are analyzed in combination with the preparation methods. The present invention controls the ternary precursor (Ni x Fe 0.66-x Mn 0.34 The Ni content in )(OH)2 is 0.35≤x≤0.45, the Ni content is increased, the Fe content is reduced, and the sintering temperature is controlled at a higher temperature of 900℃-1010℃. The high nickel content is combined with the high sintering temperature, and the two work synergistically. Due to the ionic radius Ni 2+ 0.069nm, Mn 4+ 0.053nm, Mn 3+ 0.058nm, Fe 3+ 0.055nm, Ni 2+ The ionic radius is larger than that of Mn 3+ , Mn 4+ , Fe 3+ , because Ni 2+ Size and Mn 3+ , Mn 4+ , Fe 3+ The mismatch, higher sintering temperature for Ni 2+Energy is provided by the transfer from the bulk phase to the surface. The two factors work together to make Ni 2+ It is easy to aggregate on the surface of the material, causing surface segregation, and combining with the surface oxygen to form a rock salt phase of NiO, so that the positive electrode active material has a phase with a Ni concentration gradient (three-layer coating structure), which is respectively the layered phase Na at 0-99%R from the core of the positive electrode active material particle y Ni x Fe 0.66-x Mn 0.34 O2 (0.9≤y≤1.1, 0.35≤x≤0.45), a layered phase and a rock salt phase transition phase at 99%-99.7%R from the core of the positive electrode active material particle, a rock salt phase NiO at 99.7%-100%R from the core of the positive electrode active material particle, and preferably, the molar proportion of Ni in the transition metal element in the layered phase is 33%-36%, the molar proportion of Ni in the transition metal element in the layered phase and the rock salt phase transition phase is 64%-67%, and the molar proportion of Ni in the transition metal element in the rock salt phase is 94%-97%, thereby anchoring the migration of the layered phase and the rock salt phase transition phase through the stable structure of the rock salt phase, inhibiting the phase change of the layered positive electrode active material under high voltage, reducing the unit cell volume change of the positive electrode active material, inhibiting the generation and expansion of microcracks, and controlling the ratio of the unit cell volume change rate to the capacity contribution to extend the cycle life of the sodium ion battery.

[0194] When x<0.35, the nickel in the material can be evenly distributed in the Na y Ni x Fe 0.66-x Mn 0.34There is no excess Ni at the Ni site in the O2 material, and the surface segregation conditions cannot be met. For example, in Comparative Example 1, x=0.33, due to the absence of excess Ni, the transition phase between the layered phase and the rock salt phase and the rock salt phase cannot be formed, and the positive electrode active material is prone to a low reversible P3→O3' phase transition under high voltage, which causes a large change in the unit cell volume of the positive electrode active material and produces microcracks, affecting the stability of the positive electrode active material, thereby greatly reducing the cycle life of the sodium ion battery. When x>0.45, the synthesized positive electrode active material has a high residual alkali value, which is not conducive to the processing of the material, and will cause gelation during the processing, resulting in poor performance of the positive electrode active material. For example, in Comparative Example 3, x=0.5, the Ni content is too high, and gelation is prone to occur during the processing, which makes the performance of the positive electrode active material of Comparative Example 3 deteriorate, ultimately affecting the cycle performance of the sodium ion battery. When the sintering temperature is lower than 900°C, the energy provided by the sintering is insufficient to diffuse the excess Ni inside the positive electrode active material to the surface of the positive electrode active material, and surface segregation cannot be achieved. For example, the sintering temperature of Comparative Example 2 is 850°C, and the Ni content in the rock salt phase is relatively low, which cannot effectively anchor the migration of the transition phase between the layered phase and the rock salt phase, making the positive electrode active material prone to a low reversible P3→O3' phase transition under high voltage, and the unit cell volume of the positive electrode active material changes significantly to produce microcracks, affecting the stability of the positive electrode active material, thereby greatly reducing the cycle life of the sodium ion battery. When the sintering temperature is higher than 1010°C, the Ni ions in the Ni site in the material will diffuse to the surface, and the excess Ni will migrate to the surface, causing Ni to be over-enriched on the surface, forming an overly thick surface layer of salt rock phase NiO. The overly thick surface layer of salt rock phase is not conducive to the release and embedding of sodium ions, so that the excessive segregation of nickel changes the structure of the positive electrode active material, which is not conducive to the circulation of the sodium ion battery. For example, the sintering temperature of Comparative Example 3 is 1050°C, and the sintering temperature is too high. Referring to the molar proportion of Ni in each phase in the transition metal element in Table 1, Ni is excessively segregated and excessively enriched on the surface, which destroys the structure of the positive active material, so that the positive active material has a larger unit cell volume change rate and a lower capacity contribution during the test, so that the ratio of the unit cell volume change rate of the positive active material to the capacity contribution (0.625) far exceeds the 0.05≤a≤0.14 specified in the present invention, thereby making the cycle life of the prepared sodium ion battery extremely low. In addition, the particle size D50 of the positive active material prepared by the present invention is 1-10μm, so that the positive active material has a smaller specific surface area and diffusion resistance. When the particle size D50 is less than 1μm, the specific surface area of ​​the positive active material becomes larger, and the contact area between the positive active material and the electrolyte is increased during the test, so that the gas production of the sodium ion battery increases, thereby reducing the cycle performance. When the particle size D50 is greater than 10 μm, the diffusion distance of sodium ions in the positive electrode active material increases, which increases the diffusion resistance of the positive electrode active material, resulting in an increase in the impedance of the sodium ion battery and a decrease in the cycle performance.Preferably, the particle size D50 of the positive electrode active material of the present invention is 4.5-4.8 μm, which can effectively balance the specific surface area and diffusion resistance of the positive electrode active material, while ensuring that the sodium ion battery produces less gas, reducing the impedance of the sodium ion battery, thereby ensuring the cycle performance of the sodium ion battery.

[0195] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A sodium ion battery, characterized in that: include: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, wherein the positive electrode active material is Na y Ni x Fe 0.66-x Mn 0.34 O2, wherein 0.9≤y≤1.1, 0.35≤x≤0.45, the positive electrode active material contains a phase with a Ni concentration gradient, and from the core of the positive electrode active material particle to the outside, the layered phase Na y Ni x Fe 0.66-x Mn 0.34 O2, a transition phase between a layered phase and a rock salt phase, and a rock salt phase NiO, wherein the transition phase between the layered phase and the rock salt phase is located at a distance of (95%-96%)R-(97%-99.8%)R from the core of the positive electrode active material particle, wherein R is the minimum circumscribed circle radius of the positive electrode active material, 0.9≤y≤1.1, 0.35≤x≤0.45; The molar proportion of Ni in the layered phase among the transition metal elements is 30%-36%, the molar proportion of Ni in the transition metal elements in the layered phase and the rock salt phase is 60%-70%, and the molar proportion of Ni in the transition metal elements in the rock salt phase is 90%-100%; A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; The ratio a of the unit cell volume change rate V to the capacity contribution C of the positive electrode active material satisfies 0.05≤a≤0.14; Among them, the unit cell volume change rate of the positive electrode active material V1 is the unit cell volume of the positive electrode active material of the positive electrode sheet when the sodium ion battery is discharged to 2.0V and then disassembled, and the positive electrode sheet is assembled into a button battery, and the positive electrode sheet is charged to 4.0V in the second cycle of the charge and discharge cycle; V2 is the unit cell volume of the positive electrode active material of the positive electrode sheet when the same sodium ion battery is discharged to 2.0V and then disassembled, and the positive electrode sheet is assembled into a button battery, and the positive electrode sheet is charged to 4.2V in the second cycle of the charge and discharge cycle; Capacity Contribution C1 is the capacity of the sodium ion battery in the voltage range of 4.0-4.2V during the second charging process of the battery, which is charged to 4.2V at a constant current of 1C, then charged to a current of 0.05C at a constant voltage, and then allowed to stand for 10 minutes. Then, it is discharged to 2.00V at a constant current of 1C and allowed to stand for 10 minutes. During the charge and discharge cycle of 3 times, C2 is the capacity of the sodium ion battery in the voltage range of 2-4.2V during the second charging process of the battery, which is charged to 4.2V at a constant current of 1C, then charged to a current of 0.05C at a constant voltage, and then allowed to stand for 10 minutes. Then, it is discharged to 2.00V at a constant current of 1C and allowed to stand for 10 minutes. During the charge and discharge cycle of 3 times, 2. A sodium ion battery according to claim 1, characterized in that: The ratio a of the unit cell volume change rate and the capacity contribution of the positive electrode active material satisfies 0.05≤a≤0.

09.

3. A sodium ion battery according to claim 2, characterized in that: The ratio a of the unit cell volume change rate and the capacity contribution of the positive electrode active material satisfies 0.05≤a≤0.

08.

4. A sodium ion battery according to claim 1, characterized in that: The unit cell volume change rate V satisfies 0.005≤V≤0.

014.

5. A sodium ion battery according to claim 4, characterized in that: The unit cell volume change rate V satisfies 0.005≤V≤0.

01.

6. A sodium ion battery according to claim 5, characterized in that: The unit cell volume change rate V satisfies 0.005≤V≤0.

006.

7. A sodium ion battery according to claim 1, characterized in that: The capacity contribution C satisfies 0.06≤C≤0.

12.

8. A sodium ion battery according to claim 7, characterized in that: The capacity contribution C satisfies 0.075≤C≤0.

1.

9. A sodium ion battery according to claim 1, characterized in that: The molar proportion of Ni in the transition metal elements in the layered phase is 33%-36%, the molar proportion of Ni in the transition metal elements in the transition phase between the layered phase and the rock salt phase is 64%-67%, and the molar proportion of Ni in the transition metal elements in the rock salt phase is 94%-97%.

10. A sodium ion battery according to claim 1, characterized in that: The particle size D50 of the positive electrode active material satisfies 1 μm≤D50≤10 μm.

11. A sodium ion battery according to claim 10, characterized in that: The particle size D50 of the positive electrode active material satisfies 4.5 μm≤D50≤4.8 μm.

12. A sodium ion battery according to claim 1, characterized in that: The positive electrode active material is prepared by mixing sodium carbonate with a ternary precursor (Ni x Fe 0.66-x Mn 0.34 )(OH)2 is mixed in a molar ratio of 0.9-1.1:1, sintered at 900℃-1010℃ for 15-25h, cooled to room temperature, sieved, and sealed to obtain; wherein 0.35≤x≤0.45.

Citation Information

Patent Citations

  • Positive pole active material, positive pole, and nonaqueous secondary cell

    CN102439767A

  • Method for manufacturing positive electrode active material, and secondary battery

    CN110337744A